Review of the diet for Cerdocyon thous (Carnivora: Canidae), and the first record of Bothrops moojeni (Serpentes: Viperidae) as prey - Assis, Rhayane A. [UNESP]; Benvindo-Souza, Marcelino; Borges, Rinneu E.; Montanheiro-Valentim, Alisson; Santos, Lia Raquel S. (Universidad Nacional de Colombia, 2023)
The crab-eating fox Cerdocyon thous has a diverse diet ranging from plants to vertebrates, but its diet has never been comprehensively reviewed. Here, we provide the first such review and report the first-ever record of C. thous feeding on the Brazilian lancehead Bothrops moojeni, although other Bothrops species have been documented in the diet of this fox species.
Revisión de la dieta de Cerdocyon thous (Carnivora: Canidae), y el primer registro de Bothrops moojeni (Serpentes: Viperidae) como presa
Keywords: Interspecific interactions; mammals; natural history; reptiles